Structure based Pharmacophore modeling, Virtual screening and Molecular Docking of Potential Phytochemicals against HSP70 - Sangeetha Kothandan, R. P. Sasikala, K. S. Meena (Journal of Applied Pharmaceutical Science, 2017)
Objectives: Heat shock protein 70(HSP 70) forms the central components of cellular network of molecular chaperones and is highly conserved. It is a potential anticancer target as it influences many signaling pathways. Hence the study was designed to identify the novel Phytochemicals against the substrate binding domain of HSP70 by in silico analysis.Materials and Methods: Structure based pharmacophore modeling was performed , followed by virtual screening from a library of diverse Phytochemicals to identify the potential inhibitors of HSP70, in specific ,to the substrate binding domain .Further validation of the hit compounds was done by Molecular docking and ADMET analysis in Discovery studio V4.0. Results: Pharmacophore modeling resulted in the generation of 5 feature and 6 feature pharmacophore models that identified Eleutheroside E and calamistrin D as the lead binders to the substrate binding domain of HSP70 exhibiting best fit values and high binding energy . Also, both the compounds were non mutagenic, non carcinogenic, non hepatotoxic and showed good blood brain barrier penetration efficiency by ADMET analysis.Conclusion: Thus, the identified lead Phytochemicals can be proposed for further in vitro and in vivo evaluation on the expression of HSP70.
Keywords: HSP 70, Pharmacophore modeling, Virtual screening, Molecular Docking, Phytochemicals.